Women and the comic plot in Menander - Traill, Ariana, 1969- (Cambridge University Press, 2008)
Taking a fresh look at mistaken identity in the work of an author who helped to introduce the device to comedy, in this book Professor Traill shows how the outrageous mistakes many male characters in Menander make about women are grounded in their own emotional needs. The core of the argument derives from analysis of speeches by or about women, with particular attention to the language used to articulate problems of knowledge and perception, responsibility and judgement. Not only does Menander freely borrow language, situations, and themes from tragedy, but he also engages with some of tragedy's epistemological questions, particularly the question of how people interpret what they see and hear. Menander was instrumental in turning the tragic theme of human ignorance into a comic device and inventing a plot type with enormous impact on the western tradition. This book provides original insights into his achievements within their historical and intellectual context.